1995
DOI: 10.1182/blood.v86.3.1202.bloodjournal8631202
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inactivation of the major positive regulatory element (HS-40) of the human alpha-globin gene locus

Abstract: We have examined the role of the major positive upstream regulatory element of the human alpha-globin gene locus (HS-40) in its natural chromosomal context. Using homologous recombination, HS-40 was replaced by a neo marker gene in a mouse erythroleukemia hybrid cell line containing a single copy of human chromosome 16. In clones from which HS-40 had been deleted, human alpha-globin gene expression was severely reduced, although basal levels of alpha 1 and alpha 2-globin mRNA expression representing less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…D Vernimmen et al recruitment of Pol II was severely reduced. As before, the level of a globin mRNA expression was considerably reduced (B3% of normal; Bernet et al, 1995, and data not shown). These findings show that recruitment of the complete PIC at the a globin promoter is dependent on the combined effect of the upstream elements.…”
Section: Timing Of Gene Expressionsupporting
confidence: 81%
See 4 more Smart Citations
“…D Vernimmen et al recruitment of Pol II was severely reduced. As before, the level of a globin mRNA expression was considerably reduced (B3% of normal; Bernet et al, 1995, and data not shown). These findings show that recruitment of the complete PIC at the a globin promoter is dependent on the combined effect of the upstream elements.…”
Section: Timing Of Gene Expressionsupporting
confidence: 81%
“…Grey boxes refer to previously defined multi-species conserved elements (MCS). Previously described deletions from the human a globin cluster (Bernet et al, 1995;Craddock et al, 1995) are shown as annotated (C40, IJ and MC) boxes. therefore, good candidates to be involved in triggering the transition from a poised to an active transcriptional state.…”
Section: Sp/x-kruppel-like Factors Are Recruited To the A Globin Prommentioning
confidence: 99%
See 3 more Smart Citations